2018
DOI: 10.3389/fnmol.2018.00091
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Long Non-coding RNAs and mRNAs by RNA-Sequencing in the Hippocampi of Adult Mice Following Propofol Sedation

Abstract: Propofol is a frequently used intravenous anesthetic agent. The impairment caused by propofol on the neural system, especially the hippocampus, has been widely reported. However, the molecular mechanism underlying the effects of propofol on learning and memory functions in the hippocampus is still unclear. In the present study we performed lncRNA and mRNA analysis in the hippocampi of adult mice, after propofol sedation, through RNA-Sequencing (RNA-Seq). A total of 146 differentially expressed lncRNAs and 1103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…As a known regulator of miR-21, signal transducer and activator of transcription 3 plays a key role in propofol-induced neurotoxicity by mediating the miR-21/sprout 2/Akt pathway ( Twaroski et al, 2014 ). Meanwhile, a recent RNA-sequencing analysis revealed that propofol-based sedatives may up-regulate FoxO pathway-related proteins (PI3K and Akt) and down-regulate FoxO3a at both the RNA and protein levels via differently expressed lncRNAs (lncE230001N04Rik, lncRP23-430H21.1, and lncB230206L02Rik) ( Fan et al, 2018 ). In in vitro PC-12 cells and rat brain tissues, circ-001372 suppressed propofol-induced neurotoxicity and neuroinflammation through the PI3K/Akt signaling pathway ( Wang et al, 2021a ).…”
Section: Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…As a known regulator of miR-21, signal transducer and activator of transcription 3 plays a key role in propofol-induced neurotoxicity by mediating the miR-21/sprout 2/Akt pathway ( Twaroski et al, 2014 ). Meanwhile, a recent RNA-sequencing analysis revealed that propofol-based sedatives may up-regulate FoxO pathway-related proteins (PI3K and Akt) and down-regulate FoxO3a at both the RNA and protein levels via differently expressed lncRNAs (lncE230001N04Rik, lncRP23-430H21.1, and lncB230206L02Rik) ( Fan et al, 2018 ). In in vitro PC-12 cells and rat brain tissues, circ-001372 suppressed propofol-induced neurotoxicity and neuroinflammation through the PI3K/Akt signaling pathway ( Wang et al, 2021a ).…”
Section: Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…A recent experiment using the hippocampi of adult mice has revealed a mechanism of propofol in the regulation of lncRNAs. The study showed that propofol sedation can impact the expression of lncRNAs and mRNA in the hippocampus via the FoxO pathway-related proteins phosphatidylinositol 3-kinase and protein kinase B [37]. Intriguingly, the results of microarray analysis, qPCR, and Western blot assays performed in this study showed that propofol also exhibited an anti-inflammatory effect on THP-1 macrophages via inhibiting lncRNA-LOC286367 expression.…”
Section: Discussionmentioning
confidence: 76%
“…Transcriptome RNA sequencing was carried out as described previously. 22 SNU-449 and HuH-6 cells (5 × 10 5 ) were seeded in 6-well plates and treated with 25 μg/mL propofol or equal volume of DMSO for 48 h, then cells were collected for total RNAs extraction using RNeasy Mini kit (Qiagen). NEB Next Ultra II Directional RNA Library Prep kit (New England BioLabs) was used to generate RNA-seq libraries.…”
Section: Transcriptome Rna Sequencing and Data Analysismentioning
confidence: 99%